Double cross - McMullen, Beth, 1969- (Mrs. Smith's spy school for girls, 2019)
While participating in the Challenge at Briar Academy, Abby and friends learn that their nemesis is using Briar as headquarters for planning an attack, and that the Ghost has inside help.